CHARACTERISTICS OF BRIQUETTES FROM COFFEE TREE TRUNK CHARCOAL POWDER: INFLUENCE OF DRYING TEMPERATURE ON BURNING RATE AND CALORIFIC VALUE - Yosep Adi Saputra; Danang Murdiyanto; Bernardus Crisanto Putra Mbulu (Universitas Katolik Widya Karya Malang, 2026)
Coffee tree trunks are a low-demand biomass resource with potential to be converted into higher-value products, such as charcoal briquettes. This study investigates the effect of drying temperature and particle size (Mesh 30 and Mesh 250) on the performance of coffee wood charcoal briquettes using starch as a binder. Drying was conducted at temperatures of 60°C, 80°C, and 100°C. The briquettes were tested through combustion by heating 50 ml of water, while temperature changes were recorded every minute using a thermocouple until boiling point was reached. Additional analyses included moisture content, ash content, combustion rate, and calorific value.The results show that higher drying temperatures improve briquette performance. The highest combustion rate for Mesh 30 was 0.20 g/min at 100°C, while Mesh 250 reached 0.16 g/min at the same temperature. The calorific value increased with temperature, with Mesh 30 reaching 7178.02 cal/g and Mesh 250 achieving 7498.80 cal/g at 100°C. Although Mesh 30 briquettes exhibited competitive calorific values, their combustion stability was lower compared to Mesh 250.These findings indicate that drying temperature and particle size significantly influence the quality and performance of coffee wood charcoal briquettes